Feed utilisation options for smallholder dairy farmers - Romney, Dannie L.; Tanner, J.C.; Chui, J.; Kenyanjui, M.; Morton, J.; Ndegwa, P.; Kimari, A.; Thorne, Peter J. (British Society of Animal Science, 1998)
A Participatory Rural Appraisal (PRA) was conducted with smallholder dairy farmers in the central highlands of Kenya, where smallholder mixed farming systems predominate. Shortage of fodder is the principal problem as a result of decreasing farm size and, therefore, cattle are rarely fed ad libitum. Given this constraint, the aim of the PRA was to determine whether farmers employ practices which affect feed utilisation through manipulation of intake and feeding behaviour. Do different farmers with access to the same quantity and type of feed choose to utilise those feeds in different ways? When identifying researchable issues which could allow Development of improved feeding strategies, it is important to consider novel practices which may benefit other farmers with similar resources.